Nickel Metallaphotoredox Catalysis Enabling Desulfurative Cross Coupling Reactions. Issue 24 (9th December 2022) - Geniller, Lilian; Taillefer, Marc; Jaroschik, Florian; Prieto, Alexis
Abstract: Metallaphotoredox processes have emerged as powerful methods for C−C bond formations. The Ni‐photoredox catalyzed desulfurative cross‐coupling of thiol derivatives with aryl bromides has now been established. This procedure provides access to simple and complex unsymmetrical diarylmethane molecules under mild reaction conditions with a broad functional group tolerance. The key steps of the reaction involve a silane‐mediated halogen‐atom transfer (XAT) and a subsequent intramolecular homolytic substitution (SH ), forming C ‐centered radicals from various thiol derivatives as shown by mechanistic studies. This study paves the way for new transformations of abundant, naturally occurring thiols. Abstract :